Diagnostic and Pathologic Value of Programmed Death-Ligand 1 Expression in Colon Carcinoma - Omar Helmy, Dina; Tag El-Sabah, Mahmoud; Sherif Negm, Mohamed; Armia, Mina Ezzat Onsy (Asian Pacific Journal of Cancer Biology, 2020)
Objectives: To evaluate the diagnostic value of programmed death-ligand1 expression in colon carcinoma cells and its correlation with different pathological features. Methods: An immunohistochemical study was conducted on 50 cases diagnosed as colon carcinoma over a one year period from October 2018 to October 2019.The paraffin blocks were received from the Pathology Departments, Faculty of Medicine, Cairo University and Misr University for Science and Technology (MUST). The diagnosis of colon carcinoma for all cases was revised using H&E stain. The immunohistochemical expression of programmed death- ligand1 was assessed using immune reactive score method. The personal data, clinical details and pathological diagnosis were recorded and correlated with programmed death-ligand1 expression. Results: This study included 50 cases of colon carcinoma. There was a male predominance with female to male ratio 1:1.08.The age of patients was ranged from 30 years to 76 years with mean age 53.3± 11.2 years. The majority of cases (44%) were invasive adenocarcinoma followed by invasive adenocarcinoma with mucoid activity (18%), invasive adenocarcinoma with neuroendocrine differentiation (16%), invasive signet ring carcinoma (14%) and invasive mucinous carcinoma (8%). Immune reactive score for programmed death-ligand1 had a Mean ± Standard Deviation of 8.4 ± 4.2. Strong immune reactive score was represented by 58% of cases, moderate immune reactive score was represented by 24% of cases and only one case (2%) had mild immune reactive score. The remaining 16% of cases were negative. Correlation between immune reactive score of programmed death-ligand1and tumor type, size and lymph-vascular invasion was statistically significant. Cases with marked immune reactive score for programmed death-ligand1 showed highest predilection for invasive adenocarcinoma with neuroendocrine differentiation, large sized tumors and lymph-vascular invasion. Conclusion: The expression of programmed death-ligand1 using immune reactive score method can estimate the growth of colon carcinoma, invasive adenocarcinoma with neuroendocrine differentiation and lymph-vascular spread. Further large scale studies utilizing programmed death-ligand 1can aid in identifying the prognosis and therapeutic possibilities for patients with colon cancer.